Low-alloy ultrahigh-strength steel metal powder core wire for electric arc additive manufacturing and repairing and preparation method of low-alloy ultrahigh-strength steel metal powder core wire

By using low-alloy ultra-high-strength steel metal powder core wire wrapped with pure iron tape, the problem of poor strength and plasticity matching in arc additive manufacturing and repair of existing low-alloy ultra-high-strength steel wire is solved, and the effect of high tensile strength and good plasticity is achieved without subsequent heat treatment.

CN119609451AActive Publication Date: 2025-03-14CHINA WEAPON SCI ACADEMY NINGBO BRANCH
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411545533.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-03-14
Estimated Expiration
2044-11-01

AI Technical Summary

Technical Problem

After arc additive manufacturing and repair, the existing low-alloy ultra-high strength steel wire materials have poor strength and plasticity matching, and the solid wire materials are difficult to draw and cold deformation, and the yield rate is low.

Method used

The low-alloy ultra-high strength steel metal powder core wire composed of pure iron belt and pharmaceutical powder is used. The powder contains components such as graphite, ferrosilicon powder, manganese powder, nickel powder, iron molybdenum powder, chromium powder, vanadium powder, aluminum powder and arc stabilizer, and is prepared through high-temperature baking and rolling and stirring to form a metal powder core wire material.

Benefits of technology

Under no heat treatment conditions, the tensile strength of the samples and components for additive forming or repair exceeds 1500MPa, and the elongation after break exceeds 10%. There is no need for subsequent high-temperature quenching + tempering heat treatment process, avoiding deformation and cracking caused by heat treatment of components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119609451A_ABST
    Figure CN119609451A_ABST
Patent Text Reader

Abstract

A low-alloy ultrahigh-strength steel metal powder core wire for electric arc additive manufacturing and repairing is characterized in that the low-alloy ultrahigh-strength steel metal powder core wire is composed of a pure iron strip and powder, the powder is wrapped in the pure iron strip, and the powder comprises, by weight, 1%-1.8% of graphite, 3.0%-4.0% of ferrosilicon powder, 2.8%-4.0% of manganese powder, 3.5%-5.2% of nickel powder, 4.0%-5.5% of ferromolybdenum powder, 9.5%-12% of chromium powder, 2%-4% of vanadium powder, 0.5%-1.2% of aluminum powder, 4%-7% of arc stabilizer and the balance iron powder. And the balance of pure iron powder. The invention further discloses a preparation method of the low-alloy ultrahigh-strength steel metal powder core wire. The obtained low-alloy ultrahigh-strength steel metal powder core wire has good strength and plasticity in the electric arc additive manufacturing and repairing accumulation state, and is suitable for overall manufacturing and repairing of large complex components.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an arc additive manufacturing and repairing material, and in particular to a low-alloy ultra-high-strength steel metal powder core wire. The present invention also relates to a preparation method of the low-alloy ultra-high-strength steel metal powder core wire. Background Art

[0002] Low alloy ultra-high strength steel is widely used in offshore vessels, mining machinery, weapons and equipment, rail transit and other fields due to its excellent strength and toughness, low cost and other advantages. In the manufacturing process of large and complex low alloy ultra-high strength steel components, casting, mechanical processing removal or die forging are often used. Large ultra-high strength steel components are prone to macrosegregation during casting, resulting in unstable organization and performance, and even casting defects such as looseness and shrinkage, resulting in low component yield. When large and complex components are manufactured by mechanical processing removal, the manufacturing industry chain is long, and low alloy ultra-high strength steel has high strength and hardness, severe tool wear, high processing difficulty, long manufacturing cycle, low material utilization rate, and limited complexity of large components. When manufactured by die forging, large-tonnage forging machines are required, and larger-sized molds need to be manufactured. The mold manufacturing cost is high and the cycle is long, especially for large and complex components with many types and small quantities. In addition, large and complex low alloy ultra-high strength steel components will inevitably suffer from local wear, corrosion and other damage during service, affecting the shape and dimensional accuracy of the components and service reliability. These partially damaged large-scale complex low-alloy ultra-high strength steel components have high added value, strong repairability, and great reuse benefits. However, in actual application, damaged large-scale complex low-alloy ultra-high strength steel components are often scrapped, resulting in a huge waste of resources. Therefore, the development of advanced manufacturing and repair technology for large-scale complex low-alloy ultra-high strength steel components will contribute to the high-quality construction and rapid development of major projects in my country.

[0003] In recent years, the rapid development of additive manufacturing technology has provided new methods for the manufacture and repair of large, complex, low-alloy, ultra-high-strength steel components. Among them, arc additive manufacturing technology has the characteristics of high forming efficiency and low equipment and raw material costs. It has been applied to the overall manufacturing and local repair of large, complex, low-alloy, ultra-high-strength steel components at home and abroad, greatly improving material utilization, shortening the manufacturing cycle and industrial chain, and reducing manufacturing costs. However, the current arc additive manufacturing and repair technology of large, complex, low-alloy, ultra-high-strength steel components still faces the following problems:

[0004] (1) The strength and plasticity of low-alloy ultra-high-strength steel wire alloy systems are poorly matched after arc additive manufacturing and repair. Without heat treatment, the tensile strength of arc additively manufactured components is often around 1300MPa, and the elongation after fracture does not exceed 10%. It still needs to be further optimized through heat treatment, such as through high-temperature quenching + tempering heat treatment process. However, for large and complex additively manufactured components, high-temperature quenching can easily cause deformation of the components, and even cause cracking when cooling too quickly. On the other hand, for large ultra-high-strength steel components such as rails and mining machinery, heat treatment cannot be performed after in-situ repair.

[0005] (2) At present, the arc additive manufacturing and repair of large and complex low-alloy ultra-high strength steel components mainly use solid wire. Due to the high strength and low plasticity of low-alloy ultra-high strength steel, solid wire drawing and cold deformation are difficult and the yield is low, especially for alloy systems with higher strength and higher hardness. The Chinese invention patent application with application number 202311486740.6, "A low-alloy ultra-high strength steel wire for arc additive manufacturing and its preparation method" (application publication number CN117604401A), discloses a low-alloy ultra-high strength steel solid wire alloy system with a tensile strength of up to 1300MPa in the stacked state without heat treatment during arc additive manufacturing and its preparation method, which is suitable for arc additive manufacturing of ultra-high strength steel parts with a tensile strength requirement of 1300MPa. However, when further optimizing the wire composition and improving the tensile strength of the metal in the deposited state without heat treatment during arc additive manufacturing or repair (for example, exceeding 1400MPa or even exceeding 1500MPa), the new system of low-alloy ultra-high-strength steel wire raw materials has higher strength and worse plastic deformation ability, and the deformation resistance is greater during the drawing and preparation of solid wires. Cracks are easily generated on the wire surface, and it is easy to break during subsequent drawing. The drawing die is severely worn, resulting in low yield and poor surface quality of low-alloy ultra-high-strength steel solid wires. Therefore, in order to meet the needs of arc additive manufacturing and repair of large and complex components, it is of great engineering significance to develop high-performance, easy-to-draw low-alloy ultra-high-strength steel wires. Summary of the invention

[0006] The first technical problem to be solved by the present invention is to provide a low-alloy ultra-high-strength steel metal powder core wire suitable for arc additive manufacturing and repair of large and complex components in response to the above-mentioned technical status quo.

[0007] The second technical problem to be solved by the present invention is to provide a method for preparing low-alloy ultra-high-strength steel metal powder core wire suitable for arc additive manufacturing and repair of large and complex components in response to the above-mentioned technical status quo.

[0008] The technical solution adopted by the present invention to solve the above-mentioned first technical problem is: a low-alloy ultra-high-strength steel metal powder core wire for arc additive manufacturing and repair, characterized in that it is composed of a pure iron belt and powder, the powder is wrapped in the pure iron belt, and the powder includes the following components and their weight ratios:

[0009] Graphite 1-1.8%, ferrosilicon powder 3.0-4.0%, manganese powder 2.8-4.0%, nickel powder 3.5-5.2%, ferromolybdenum powder 4.0-5.5%, chromium powder 9.5-12%, vanadium powder 2-4%, aluminum powder 0.5-1.2%, arc stabilizer 4-7%, and the balance is pure iron powder.

[0010] Graphite: It is used to transition carbon elements into the molten pool, and is dissolved into the martensite matrix during the rapid cooling process of additive manufacturing, producing a strong solid solution strengthening effect. Carbon elements can form vanadium carbide precipitation phases with vanadium elements, which has a precipitation strengthening effect. In addition, carbon elements can increase the dislocation density in martensite, promote the in-situ precipitation of vanadium carbide under the action of arc additive manufacturing thermal cycles, and produce a strengthening effect during the additive process without the need for subsequent heat treatment processes. However, when the carbon element is too high, it will increase the crack sensitivity during arc additive manufacturing or repair, and it is easy to produce coarse primary phases during the solidification process of arc additive manufacturing. It will also cause the vanadium carbide to coarsen, and the mismatch relationship between it and the martensite matrix will change from coherent and semi-coherent to incoherent, reducing strength and plasticity. Therefore, the mass fraction of graphite in the present invention is controlled at 1-1.8%.

[0011] Ferrosilicon powder: used to transfer silicon element into the molten pool, produce deoxidation effect, and control the fluidity of the molten pool. When the mass fraction of silicon element is too high, it is easy to produce oxide inclusions in the molten pool, and the fluidity of the molten pool will increase, and the formability of arc additive or repair space will deteriorate. Therefore, the mass fraction of ferrosilicon in the present invention is controlled at 3.0-4.0%.

[0012] Manganese powder: used to transfer manganese to the molten pool. Manganese and silicon can produce a composite deoxidation effect. The density of the formed oxide is small and it is easy to float out of the molten pool. However, manganese is an austenite stabilizing element. If the manganese content is too high, it is easy to produce residual austenite during the additive manufacturing cooling process, which reduces the strength and hardness of the additive component. In addition, too much manganese will cause excessive smoke and dust during the additive manufacturing process. Therefore, the mass fraction of manganese powder in the present invention is controlled at 2.8-4.0%.

[0013] Ferro-molybdenum powder: Molybdenum element is transferred to the molten pool, and is supersaturated in the martensite matrix during the rapid cooling process of arc additive manufacturing and repair, producing solid solution strengthening, while increasing the martensite forming ability. Under the heat treatment of multiple thermal cycles, it can promote the in-situ precipitation of vanadium carbide and improve the precipitation strengthening effect. However, when the molybdenum content is too high, coarse primary phases are easily generated during the solidification process of arc additive manufacturing, which deteriorates the strength and plastic toughness of the additive component. Therefore, the mass fraction of ferro-molybdenum powder in the present invention is controlled at 4.0-5.5%.

[0014] Chromium powder: Chromium elements are transferred to the molten pool, and cooperate with carbon elements to promote the formation of dislocations in martensite during the cooling process of additive manufacturing, provide nucleation sites for the precipitation of vanadium carbide, and promote the in-situ dispersion and precipitation of vanadium carbide under the thermal cycle of arc additive manufacturing. It is not easy to coarsen and maintains a coherent or semi-coherent relationship with the martensite matrix, resulting in precipitation strengthening. At the same time, chromium elements have a strong solid solution strengthening effect. However, when the chromium element is excessive, it is easy to segregate between dendrites during the additive solidification process, and it is easy to form a coarse precipitate phase under the action of thermal cycles, which reduces strength and toughness. Therefore, the mass fraction of chromium powder in the present invention is controlled at 9.5-12%.

[0015] Nickel powder: used to transition nickel elements into the molten pool. Nickel elements can improve the plasticity and toughness of low-alloy ultra-high-strength steel manufactured by arc additive manufacturing. During rapid cooling of additive manufacturing, it can increase the dislocation density in martensite, promote the in-situ precipitation of vanadium carbide under thermal cycling, and produce a strengthening effect. In addition, since the present invention adopts a higher carbon content and chromium content, the strength is high. In order to ensure high strength and good plasticity and toughness at the same time, a higher nickel content is required. However, nickel is an austenitizing element. When it is excessive, it will segregate during the solidification process of additive manufacturing, resulting in the production of residual austenite, which reduces the strength and hardness of the additive component. Therefore, the mass fraction of nickel powder in the present invention is controlled at 3.5-5.2%.

[0016] Vanadium powder: The vanadium element is transferred to the molten pool. Under the action of the arc additive manufacturing thermal cycle, vanadium can be precipitated in the martensite matrix in the form of vanadium carbide, maintaining a coherent and semi-coherent relationship with the martensite matrix, capturing hydrogen atoms, reducing the local hydrogen concentration, and improving the arc additive manufacturing's resistance to hydrogen embrittlement cracking. At the same time, it produces a significant precipitation strengthening effect, improving the strength while maintaining a certain degree of plasticity and toughness. However, when the vanadium element is too high, it will increase costs, cause carbide coarsening, weaken the strengthening effect, and endanger plasticity and toughness. At the same time, excessive precipitation of vanadium carbide will reduce the carbon content in the martensite matrix, weaken the interstitial strengthening effect, and further reduce the strength. Therefore, the mass fraction of vanadium powder in the present invention is controlled at 2-4%.

[0017] Aluminum powder: Aluminum elements are transferred to the molten pool to produce deoxidation, but when the aluminum content is too high, a large number of inclusions will be produced, and the crack sensitivity of additive manufacturing will be increased. Therefore, the mass fraction of aluminum powder in the present invention is controlled at 0.5-1.2%.

[0018] Arc stabilizer: It has the function of stabilizing the arc. It is a mixture of potassium titanate, sodium titanate, bismuth oxide and fluoride. When the content of the arc stabilizer is too low, the arc is unstable during the additive process. When the content of the arc stabilizer is too high, it is easy to cause inclusions, and it will increase the slag thickness and adhesion of the metal surface of the additive manufacturing, affecting the continuous additive manufacturing process. Therefore, the mass fraction of the arc stabilizer in the present invention is controlled at 4-7% of the arc stabilizer.

[0019] Furthermore, the low alloy ultra-high strength steel metal powder core wire is used in additive manufacturing and repairing metals. The aforementioned additive manufacturing and repairing metals include the following components and their weight ratios:

[0020] C: 0.20~0.35%, Si: 0.5~1.0%, Mo: 1.0~3.0%, Cr: 2.5~4.0%, Ni: 1.0~3.0%, Mn: 0.5~1.5%, V: 0.4~1.2%, Al: ≤0.1%, Fe is the balance.

[0021] The technical solution adopted by the present invention to solve the above second technical problem is: a method for preparing low alloy ultra-high strength steel metal powder core wire for arc additive manufacturing and repair, characterized by comprising the following steps:

[0022] ① Preparation of drug powder: Mix the drug powder raw materials according to the required ratio and bake them at high temperature. After cooling, put them into a blender and crush and stir them to mix them evenly. Then adjust the adsorption properties and set them aside.

[0023] ② Powder filling and wire drawing: Roll the pure iron strip into a U-shape, add the powder prepared in step ① into the U-shaped groove, close and overlap the U-shaped groove to make the powder filling compact, and then prepare it into low-alloy ultra-high-strength steel metal powder core wire for arc additive manufacturing and repair through multiple drawing passes.

[0024] Preferably, the diameter of the low alloy ultra-high strength steel metal powder core wire for arc additive manufacturing and repair is 1.2 mm.

[0025] Preferably, the particle size of the medicinal powder raw materials is 80-180 mesh.

[0026] Preferably, the high temperature baking temperature is 700-900° C., and the baking time is 5-9 hours.

[0027] Preferably, the rolling and stirring mixing time is 6 to 12 hours.

[0028] Preferably, the adsorption regulation adopts an electrostatic adsorption generator to increase the adsorption time to 10 to 20 minutes.

[0029] Preferably, in step ②, the width of the pure iron strip is 10 mm, the thickness is 0.35 mm, and the powder filling rate is 28-32%.

[0030] Compared with the prior art, the advantages of the present invention are: the composition design of the low-alloy ultra-high-strength steel metal powder core wire of the present invention is based on the arc additive manufacturing metallurgical process, and by adding chromium, molybdenum, carbon and other elements and controlling their content without affecting the crack sensitivity and formability of the arc additive manufacturing, a large number of dislocations are formed in the martensite matrix during the arc additive manufacturing and repair process, and the vanadium carbide is dispersed and precipitated at the dislocation under the heat treatment of multiple thermal cycles of the arc additive, and the relationship between the vanadium carbide and the martensite matrix is ​​coherent and semi-coherent, which produces a significant strengthening effect without damaging the plasticity. When the low-alloy ultra-high-strength steel metal powder core wire is used for arc additive manufacturing and repair, under the condition of no heat treatment, the tensile strength of the additively formed or repaired specimens and components exceeds 1500MPa, and the elongation after fracture exceeds 10%, and there is no need for subsequent high-temperature quenching + tempering heat treatment process, thereby avoiding the deformation and cracking problems caused by high-temperature heat treatment of large and complex arc additive manufacturing components, and also solving the problem of difficult heat treatment after arc additive in-situ repair of large and complex components.

[0031] The low-alloy ultra-high-strength steel metal powder core wire of the present invention adopts a design in which the powder is wrapped in a pure iron shell. Compared with conventional ultra-high-strength steel solid wire, the pure iron shell has good plasticity and the metal powder core wire has good drawing formability. It can solve the current problems of high difficulty in drawing low-alloy ultra-high-strength steel solid wire and low yield, and is particularly suitable for low-alloy ultra-high-strength steel wire alloy systems with high strength, high hardness and difficulty in deformation.

[0032] The low-alloy ultra-high-strength steel metal powder core wire of the present invention has low alloy content, low raw material cost, good arc additive and repair formability, stable process, low crack sensitivity, can meet the requirements of continuous additive manufacturing, and is suitable for arc additive manufacturing and repair of low-alloy ultra-high-strength steel components with a tensile strength exceeding 1500MPa. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is a schematic cross-sectional view of the low alloy ultra-high strength steel metal powder core wire obtained in Example 1. DETAILED DESCRIPTION

[0034] The present invention is further described in detail below with reference to the accompanying drawings.

[0035] Example 1

[0036] A low alloy ultra-high strength steel metal powder core wire for arc additive manufacturing and repair, comprising a pure iron strip and powder, wherein the powder is wrapped in the pure iron strip, and the powder is mixed with multiple components, specifically as follows:

[0037] Graphite 1%, ferrosilicon powder 3.2%, manganese powder 2.8%, nickel powder 3.6%, ferromolybdenum powder 4.4%, chromium powder 10.2%, vanadium powder 3.3%, aluminum powder 0.8%, arc stabilizer 4.4%, and pure iron powder as the balance.

[0038] The particle sizes of all components of the medicine powder are 80-180 meshes, and the pure iron belt has a width of 10 mm and a thickness of 0.35 mm.

[0039] The specific steps of the method for preparing low alloy ultra-high strength steel metal powder core wire for arc additive manufacturing and repair are as follows:

[0040] (1) Preparation of drug powder: The above-mentioned drug powders were mixed according to the proportion and baked at 760°C for 9 hours. After cooling, they were put into a blender and rolled and stirred for 6 hours to mix evenly. Then, they were placed in an electrostatic adsorption generator for 10 minutes to adjust the adsorption of the drug powders and then used for later use.

[0041] (2) Powder filling and wire drawing: The pure iron strip is rolled into a U-shape, and the powder prepared in step (1) is added into the U-shaped groove. The U-shaped groove is closed and overlapped to make the powder filled tightly. The filling rate is 28%. The structure is shown in FIG. Figure 1 As shown, the pure iron strip 1 wraps the powder 2. After multiple drawing passes, the diameter changes from Φ2.8 to Φ2.4 to Φ1.8 to Φ1.4 to Φ1.2 mm, and then the product is dried and wound into a coil.

[0042] Arc additive manufacturing and repair tests were carried out using a Fronius CMT welding power source, with a wire feeding speed of 5 m / min, a welding gun moving speed of 3.5 mm / s, pure carbon dioxide as the shielding gas, and a gas flow rate of 15 L / min. Block specimens with a size of 150 mm × 100 mm × 50 mm were manufactured by additive manufacturing. The composition of the additively manufactured and repaired block metal is shown in Table 1. M10 standard tensile specimens were cut along the direction of the welding gun movement, and room temperature tensile tests were carried out. The measurements were taken three times and the average value was calculated. The tensile properties are shown in Table 2.

[0043] Example 2

[0044] A low alloy ultra-high strength steel metal powder core wire for arc additive manufacturing and repair, comprising a pure iron strip and powder, wherein the powder is wrapped in the pure iron strip, and the powder is mixed with multiple components, specifically as follows:

[0045] Graphite 1.6%, ferrosilicon powder 3.3%, manganese powder 3.6%, nickel powder 4.6%, ferromolybdenum powder 5.2%, chromium powder 11%, vanadium powder 3.6%, aluminum powder 0.93%, arc stabilizer 5.4%, and pure iron powder as the balance.

[0046] The particle sizes of all components of the medicine powder are 80-180 meshes, and the pure iron belt has a width of 10 mm and a thickness of 0.35 mm.

[0047] The specific steps of the method for preparing low alloy ultra-high strength steel metal powder core wire for arc additive manufacturing and repair are as follows:

[0048] (1) Preparation of drug powder: The above-mentioned drug powders were mixed according to the proportion and baked at 840°C for 8 hours. After cooling, they were put into a blender and rolled and stirred for 9 hours to mix evenly. Then, they were placed in an electrostatic adsorption generator for 15 minutes to adjust the adsorption of the drug powders and then used for later use.

[0049] (2) Powder filling and wire drawing: The pure iron strip is rolled into a U-shape, and the powder prepared in step (1) is added into the U-shaped groove. The U-shaped groove is closed and overlapped to make the powder filled tightly. The filling rate is 28%. Multiple drawing passes are performed, and the diameter changes from Φ2.8 to Φ2.5 to Φ2.2 to Φ1.9 to Φ1.5 mm to Φ1.2 mm. The wire is then dried and wound into a coil.

[0050] The arc additive manufacturing and repair tests were carried out using a Fronius CMT welding power source, with a wire feeding speed of 6 m / min, a welding gun moving speed of 5 mm / s, pure carbon dioxide as the shielding gas, and a gas flow rate of 20 L / min. Block specimens with a size of 150 mm × 100 mm × 50 mm were manufactured by additive manufacturing. The composition of the additively manufactured and repaired block metal is shown in Table 1. M10 standard tensile specimens were cut along the direction of the welding gun movement, and room temperature tensile tests were carried out. The measurements were taken three times and the average value was calculated. The tensile properties are shown in Table 2.

[0051] Example 3

[0052] A low alloy ultra-high strength steel metal powder core wire for arc additive manufacturing and repair, comprising a pure iron strip and powder, wherein the powder is wrapped in the pure iron strip, and the powder is mixed with multiple components, specifically as follows:

[0053] Graphite 1.8%, ferrosilicon powder 3.8%, manganese powder 4.0%, nickel powder 4.8%, ferromolybdenum powder 5.5%, chromium powder 11.8%, vanadium powder 3.8%, aluminum powder 1.1%, arc stabilizer 6.7%, and pure iron powder as the balance.

[0054] The particle sizes of all components of the medicine powder are 80-180 meshes, and the pure iron belt has a width of 10 mm and a thickness of 0.35 mm.

[0055] The specific steps of the method for preparing low alloy ultra-high strength steel metal powder core wire for arc additive manufacturing and repair are as follows:

[0056] (1) Preparation of drug powder: The above-mentioned drug powders were mixed according to the proportion and baked at 900°C for 5 h. After cooling, they were put into a blender and rolled and stirred for 12 h to mix evenly. Then, they were placed in an electrostatic adsorption generator for 20 min to adjust the adsorption of the drug powders and then used for later use.

[0057] (2) Powder filling and wire drawing: The pure iron strip is rolled into a U-shape, and the powder prepared in step (1) is added into the U-shaped groove. The U-shaped groove is closed and overlapped to make the powder filled tightly. The filling rate is 31%. Multiple drawing passes are performed, and the diameter changes from Φ2.8 to Φ2.6 to Φ2.4 to Φ2.2 to Φ2.0 mm to Φ1.8 mm to Φ1.5 mm to Φ1.2 mm. The wire is then dried and wound into a coil.

[0058] The arc additive manufacturing and repair tests were carried out using a Fronius CMT welding power source, with a wire feeding speed of 8 m / min, a welding gun moving speed of 6 mm / s, pure carbon dioxide as the shielding gas, and a gas flow rate of 25 L / min. The block specimens with a size of 150 mm × 100 mm × 50 mm were manufactured by additive manufacturing. The composition of the additively manufactured and repaired block metals is shown in Table 1. M10 standard tensile specimens were cut along the direction of the welding gun movement, and room temperature tensile tests were carried out. The measurements were taken three times and the average value was calculated. The tensile properties are shown in Table 2.

[0059] Comparative Example 1

[0060] Commercial ultra-high strength maraging steel solid wire MARVAL 18S ​​is used as a comparative example. The wire alloy composition is Fe-18.2% Ni-8.2% Co-4.7% Mo-0.44Ti-0.11% Al, the wire diameter is 1.2 mm, and the sample is manufactured by plasma arc additive manufacturing method. Argon is used as the shielding gas, the current is 180A, the wire feeding speed is 1.8m / min, and the welding gun scanning speed is 0.3m / min. The tensile specimen is taken along the running length of the welding gun, and the tensile performance test is carried out. The average value is calculated by three measurements. The mechanical properties are shown in Table 2.

[0061] Comparative Example 2

[0062] A secondary hardened ultra-high strength steel Aermet100 solid wire was used as a comparative example. The wire alloy composition was Fe-11.5% Ni-13.2% Co-3% Cr-1.2% Mo-0.22% C, and the wire diameter was 1.2 mm. The arc additive manufacturing test was carried out using a Fronius CMT welding power source. The wire feeding speed was 8 m / min, the welding gun moving speed was 5 mm / s, pure argon was used as the shielding gas, and the gas flow rate was 20 L / min. M10 standard tensile specimens were cut along the moving direction of the welding gun, and a room temperature tensile test was carried out. The measurements were taken three times and the average value was calculated. The tensile properties are shown in Table 2.

[0063] Comparative Example 3

[0064] A die steel H13 ultra-high strength steel solid wire is used as a comparative example. The wire alloy composition is Fe-5% Cr-1.5% Mo-1% V-0.35% C, and the wire diameter is 1.2 mm. The arc additive manufacturing test is carried out using a Fronius CMT welding power source. The wire feeding speed is 6.5 m / min, the welding gun moving speed is 80 cm / min, Ar+25% CO2 mixed gas is used as the shielding gas, and the gas flow rate is 12 L / min. The tensile specimen is cut along the moving direction of the welding gun, and a room temperature tensile test is carried out. The measurement is performed three times and the average value is calculated. The tensile properties are shown in Table 2.

[0065] Table 1 Example Low alloy ultra-high strength steel metal powder core wire arc additive manufacturing and repair of bulk metal alloy composition: (weight percentage)

[0066] C Si Mo Cr Ni Mn V Al Example 1 0.22 0.54 1.21 2.62 1.31 0.65 0.54 0.043 Example 2 0.29 0.62 2.16 3.06 2.25 0.92 0.72 0.061 Example 3 0.32 0.82 2.62 3.89 2.64 1.25 0.98 0.074

[0067] Table 2 Room temperature tensile properties test results of arc additive manufacturing deposited body specimens of low alloy ultra-high strength steel metal powder core wire of Example and ultra-high strength steel wire of Comparative Example:

[0068]

[0069] The low-alloy ultra-high-strength steel metal powder core wire of the present invention is easy to draw and prepare, has a low alloy element content, does not contain precious elements such as Co, and has a low wire cost; when the Fronius CMT welding power source is used for arc additive manufacturing and repair, the process is stable and the formability is good. Under the condition of stacking state without heat treatment, the tensile strength of the sample and component formed or repaired by additive manufacturing exceeds 1500MPa, and the elongation after fracture is not less than 10%, with good strength and plasticity, and no subsequent high-temperature quenching + tempering heat treatment process is required, thereby avoiding the problem of component heat treatment deformation and cracking. Comparative Example 1 Ultra-high-strength martensitic aging steel contains a large amount of cobalt, nickel and other elements, and has high cost. When used for arc additive manufacturing, under the condition of stacking state and without heat treatment, the tensile strength is lower than 1150MPa. Even after quenching + tempering, it is still lower than the arc additive manufacturing deposit prepared by the low-alloy ultra-high-strength steel wire of the present invention. Comparative Example 2 is difficult to prepare by drawing the secondary hardened ultra-high strength steel wire, has a low wire forming rate, contains a large amount of cobalt and nickel elements, and has a much higher cost than the low alloy ultra-high strength steel wire of the present invention. The arc additive manufacturing sample has a tensile strength of 1420MPa without heat treatment, and the elongation after fracture is only 6%, which is lower than the low alloy ultra-high strength steel wire of the present invention. Comparative Example 3 is a commonly used mold steel H13 wire, which is often used for mold repair. The wire preparation is difficult and contains a large amount of carbon elements. The arc additive crack sensitivity is high, and the arc additive manufacturing process needs to be strictly controlled. For example, additional preheating and slow cooling measures are required. It is not suitable for additive manufacturing of large and complex ultra-high strength steel components. Under the arc additive manufacturing stacking state, the tensile strength is only 1303MPa, and the elongation after fracture is 8.6%, which is also lower than the low alloy ultra-high strength steel wire of the present invention.

[0070] The low-alloy ultra-high-strength steel metal powder core wire of the present invention is suitable for arc additive manufacturing and repair of ultra-high-strength steel components, and is also suitable for welding connection and surfacing of ultra-high-strength steel components requiring high strength and high hardness.

[0071] The technical means disclosed in the scheme of the present invention are not limited to the technical means disclosed in the above-mentioned implementation mode, but also include technical schemes composed of any combination of the above-mentioned technical features. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications are deemed to be within the protection scope of the present invention.

Claims

1. A low alloy ultra-high strength steel metal powder core wire for arc additive manufacturing and repair, characterized in that It is composed of a pure iron belt and medicine powder, wherein the medicine powder is wrapped in the pure iron belt, and the medicine powder includes the following components and their weight ratios: Graphite 1-1.8%, ferrosilicon powder 3.0-4.0%, manganese powder 2.8-4.0%, nickel powder 3.5-5.2%, ferromolybdenum powder 4.0-5.5%, chromium powder 9.5-12%, vanadium powder 2-4%, aluminum powder 0.5-1.2%, arc stabilizer 4-7%, and the balance is pure iron powder.

2. The low alloy ultra-high strength steel metal powder core wire for arc additive manufacturing and repair according to claim 1, the low alloy ultra-high strength steel metal powder core wire is used for additive manufacturing and repairing metal, characterized in that The aforementioned additive manufacturing and repair metals include the following components and their weight ratios: C: 0.20~0.35%, Si: 0.5~1.0%, Mo: 1.0~3.0%, Cr: 2.5~4.0%, Ni: 1.0~3.0%, Mn: 0.5~1.5%, V: 0.4~1.2%, Al: ≤0.1%, Fe is the balance.

3. A method for preparing low alloy ultra-high strength steel metal powder core wire for arc additive manufacturing and repair according to claim 1 or 2, characterized in that The steps include: ① Preparation of drug powder: Mix the drug powder raw materials according to the required ratio and bake them at high temperature. After cooling, put them into a blender and crush and stir them to mix them evenly. Then adjust the adsorption properties and set them aside. ② Powder filling and wire drawing: Roll the pure iron strip into a U-shape, add the powder prepared in step ① into the U-shaped groove, close and overlap the U-shaped groove to make the powder filling compact, and then prepare it into low-alloy ultra-high-strength steel metal powder core wire for arc additive manufacturing and repair through multiple drawing passes.

4. The preparation method according to claim 3, characterized in that The diameter of the low-alloy ultra-high-strength steel metal powder core wire for arc additive manufacturing and repair is 1.2 mm.

5. The preparation method according to claim 3, characterized in that The particle size of the medicinal powder raw materials is 80-180 meshes.

6. The preparation method according to claim 3, characterized in that The high temperature baking temperature is 700-900° C., and the baking time is 5-9 hours.

7. The preparation method according to claim 3, characterized in that The rolling and stirring mixing time is 6 to 12 hours.

8. The preparation method according to claim 3, characterized in that The adsorption regulation adopts an electrostatic adsorption generator to increase the adsorption time to 10 to 20 minutes.

9. The preparation method according to claim 3, characterized in that In step ②, the width of the pure iron strip is 10 mm, the thickness is 0.35 mm, and the powder filling rate is 28-32%.

Citation Information

Patent Citations

  • Metal powder cored wire specially used for hot-working die repair

    CN105081610A

  • Metal type powder core wire material, preparation method and application

    CN110560681A

  • High-aluminum ferrite heat-resistant steel and preparation method thereof

    CN112501510A

  • Metal powder core flux-cored wire for high-strength steel and preparation method of metal powder core flux-cored wire

    CN115870666A

  • Low-alloy ultrahigh-strength steel wire material for electric arc additive manufacturing and preparation method of low-alloy ultrahigh-strength steel wire material

    CN117604401A